Theranostics An Old Concept in New Clothing - Eppard, Elisabeth (IntechOpen, 2021)
In recent years, due to advancing technology and diagnostic and therapeutic techniques, medicine and health care have become more patient-oriented. This concept of personalized medicine or theranostics can be traced back to the beginnings of nuclear medicine when radioisotopes were uncovered as diagnostic and therapeutic tools. Nowadays, the field of theranostics is in flux, as new techniques and materials allow a growing range of applications beneficial for patients. This book examines new developments in theranostics and provides a comprehensive overview of the state of the art in this exciting discipline.